Psychological and Physiological Profiles in Oncology Caregivers: A Multivariable Cross-Sectional Study - García, Esther; Aguiló, Sira; Arza, Adriana; Garzón-Rey, Jorge M.; Aguilóa, Jordi (Transactions on Engineering and Computing Sciences, 2017)
Scientific research has led to enhanced medical assistance, and hence higher disease control and a continuous lifespan dilation. However, research mainly focusses on the patient’s condition, and, in some cases, caregivers’ health is undervalued. In this paper, a close-related emotionally involved caregiver group is examined and compared to a non-caregiver group in order to investigate the role of chronic stress in their psychological and physiological state. For this purpose, blood, saliva, and hair samples, physiological signals and three validated psychometric tests are collected from both groups. Results from 39 subjects show interesting significant differences among all the psychometric profiles between the two groups although no sufficient biochemical data supports the relation with potential health consequences.